Green Turtle Conservation in the Genomic Era—Monitoring an Endangered Mediterranean Population and Its Breeding Habits - Talya Ohana; Larissa S. Arantes; Gili Tikochinski; Reut Cohen; Olga Rybak; Adi Gaspar; Sarah Sparmann; Susan Mbedi; Yaniv Levy; Camila J. Mazzoni; Yaron Tikochinski (Ecology and Evolution)
ABSTRACT The Mediterranean Sea green turtle population, confined to the eastern basin, is classified as endangered by the IUCN. The small Israeli nesting population significantly contributes to the genetic variability of the Mediterranean population, underscoring the importance of Israeli shores as a key migration route. The Israeli rescue center has established the only active breeding stock in the Mediterranean, with considerable time and effort invested in its inception and operation. Here, we present a new genomic approach aimed at maximizing this population's genetic contribution to the Mediterranean. We studied 269 green turtles from both the breeding stock and the natural Mediterranean population using mitochondrial DNA short tandem repeat (STR) haplotyping and genomic double‐digest RAD sequencing. Our analysis identified multiple degrees of kinship among individuals and aided in detecting female breeding habits. We analyzed 84 nests laid along the Israeli shores over the past 20 years and identified 60 mating events involving 35 nesting females. By incorporating females identified in previous studies, we estimate that at least 51 females have nested along the Israeli coastline during this period—a number significantly higher than earlier estimates. Furthermore, at least 59 males participated in these 60 mating events, highlighting a greater‐than‐expected level of genetic diversity within this population. We confirmed documented reproductive behaviors such as sperm conservation and multiple paternity. Additionally, we determined nesting intervals both within and between years. While our results supported the well‐documented philopatric characteristics of green turtle females, they also revealed that some females laid eggs up to 90 km apart. This genomic‐assisted evaluation offers crucial insights into the genetic variability and breeding habits of the Israeli green turtle population, providing a valuable model for conservation efforts across the Mediterranean region.